Histological Variants of Papillary Thyroid Cancer in Relation to Clinical and Morphological Parameters and Prognosis - Ivanov, A. A.; Bakarev, M. A.; Lushnikova, E. L. (Bulletin of experimental biology and medicine, 2023)
The correlation of histological features of papillary thyroid cancer with clinical and morphological prognostic factors and cause-specific mortality was analyzed in a case-control study within a cohort of patients from the Altai Regional Oncology Center (25 cases with lethal outcome and 64 follow-up controls). Significant variability was revealed in the histological structure of papillary thyroid cancer with the prevalence of classic (62%) and less frequent follicular (19%), tall cell (8%), and solid (7%) variants. In comparison with the classic variant, the solid variant was more often associated with male sex and large tumor size; follicular and tall cell variant was associated with more frequent metastases to regional lymph nodes; follicular and solid variants were associated with an increased proportion of cases with disease stages III-IV. The main differences reflecting the effect of histological factor on the disease outcome were associated with the solid variant of papillary thyroid cancer that was detected in 21% of lethal cases and only in 2% of control subjects. The detection of this variant can be of importance as an additional prognostic factor of the postoperative survival in papillary thyroid cancer.